INFLUENCE OF SILANE HEAT TREATMENT ON THE TENSILE BOND STRENGTH BETWEEN EX-3 SYNTHETIC VENEERING PORCELAIN AND COMPOSITE RESIN USING FIVE DIFFERENT ACTIVATION TEMPERATURES - Spartak Yanakiev; Bozhidar Yordanov; Valentin Dikov (Peytchinski Publishing, 2017)
Purpose: The purpose of the present study is to assess the effect of five different silane activation temperatures and eight activation methods on the tensile bond strength between one veneering porcelain and one composite resin material. Material and methods: A total of 81 ceramic rods were made of EX-3 veneering ceramic (Kuraray Noritake Dental, Japan). Sintered ceramic bars were grinded with diamond disks to size 10x2x2mm ± 0,05mm. The front part of each bar was polished. After ultrasonic cleaning in distilled water, the specimens were divided into nine groups. Silane was activated with air at room temperature, 38º С, 50º С, 100º С, 120º С using a custom made blow drier. In a silicone mold, a composite resin Z250 (3М ESPE, St. Paul, USA) was condensed toward the bond ceramic surface. A total of 81 specimens approximately 2,0 cm long were prepared for tensile bond testing. One way ANOVA, followed by Bonferroni and Games-Howell tests were used for statistical analysis. Results: The lowest tensile bond strength was observed in the control group (3,51MPa). Group 2 yielded the highest bond strength among all groups (19,54MPa). Silane heat treatment enhanced the bond strength for all treatment methods. Within the polished specimens, the highest bond strength was yielded with warm air at 120ºС (11,31MPa). Conclusion: The most effective method for bonding Z250 composite resin to EX-3 veneering ceramic includes HF etching, silane, and adhesive resin. The most effective heat treatment method for bonding is hot air at 120ºС.